ENHANCING SPEAKING SKILL IN EFL SETTING IN WEST BORNEO: A COMPARATIVE STUDY BETWEEN ROLE PLAY AND DEBATE - Efrika Siboro; Antonius Setyawan Sugeng Nur Agung; Elva Utami; Allvian Ika Fiki Susanto; Oxtapianus Tawarik; Titis Dewi Cakrawati (PROJECT (Professional Journal of English Education), 2024)
This study aims to determine the difference between using role-play and debate methods on students' speaking skills in English subject. This study is quantitative research with a comparative study method. The sample of this study was the students of XI IIS3 and XI MIA1 at one of the top-favourite private schools in one of the developed regencies in West Borneo. The researchers applied a performance test to collect the data while the T-test was used to analyze the data. The result revealed there was a significant difference between using role-play and debate toward the students' speaking skills. It can be seen from the significant difference in the comparison of their average values. In the role-play method, the average value is 62.11 while in the debate is 51.82. Thus, it can be concluded that the use of the role-play method is better than the debate method in an EFL setting. However, this study realizes that it happens because the role-play method offers a flexible chance for the students to ask for help during the preparation of the speech production.